PENGARUH PERLAKUAN AWAL UMBI DAN APLIKASI MEDIA TANAM TERHADAP PERTUMBUHAN DAN HASIL LEMPUYANG GAJAH {Zingiber zerumbet (L.) J.E. Smith}' - Sri Budi Sulianti (BERITA BIOLOGI, 2008)
Zingiber zerumbet (L.) J.E. Smith, usually called as lempuyang gajah is belonging into Zingiberaceae. This plant has been used as traditional medicine for curing coach, asma, headache, diarrhoe and disentry. Objective of study was to determine the effect of pretreatment and growth media on the productivity of Z. Zerumbet. Research was conducted in Treub Experimental Garden,Research Centre for Biology-The Indonesian Institute of Science (LIPI), Bogor. The experiment using a Factorial Completely Randomized Design with two main factors in five replications. The first factor was pretreatment of rhizome (no treatment and pretreatment on growth chamber); the second factor was growth media i.e. soil, soil+sand+cow manure (1:1:2) and soil+sand+cow manure+compost (1:1:2:2.). The result showed that pretreatment of rhizome had significant effect on number of shoots, no pretreatment of rhizome sicnificantly had higher value. Growth media had significant effects on growth and yield which had the highest value on all parameters observed. There was an interaction effect of rhizome pretreatmnent and growth media. The best result was on the combination treatment of no pretreatment rhizome and mixed media of soil+sand+cow manure+compost(1:1:2:2.) which had the highest dry weight of rhizome.